Climate Change and International Shipping The Regulatory Framework for the Reduction of Greenhouse Gas Emissions - Shi, Yubing (Brill, 2016)
In Climate Change and International Shipping: The Regulatory Framework for the Reduction of Greenhouse Gas Emissions, Yubing Shi provides ground-breaking analyses of the evolving regulatory framework for the reduction of greenhouse gas emissions from international shipping. This book examines the applicability of international environmental law principles to the reduction of greenhouse gas emissions from ships and assesses the responses of the key stakeholders to the challenge of regulation. Based on these in-depth analyses, Shi identifies key gaps in the current regulatory framework for the reduction of greenhouse gas emissions from international shipping, and proposes options for legal and institutional reforms to improve the system in place.